KEBIJAKAN PEMERINTAH THAILAND BERPARTISIPASI DI ASEAN TOURISM FORUM (ATF) DALAM MENINGKATKAN INDUSTRI PARIWISATA TAHUN 2011-2015 - Dwi Putri Fajryani; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the policy of Thailand Government participate in the implementation of the ATF in the improvement of the tourism industry in 2011-2015. ASEAN Tourism Forum is a forum of the largest tourism in the ASEAN region. These activities are routinely held each year involving all sectors of the tourism industry from all member countries of ASEAN. In 2011, ATF meeting held in Phnom Penh, Cambodia agree on some specific strategies in the field of tourism which aims to make ASEAN as a single destination for foreign tourists. Earlier, Thailand by Prime Minister Thaksin Shinawatra has proposed the idea of a single application of the visa in the sub-region ASEAN. The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from the books, encyclopedia, journal, mass media and websites to analyze the policy of Thailand Government participate in the implementation of the ATF in the improvement of the tourism industry in 2011-2015. The theories applied in this research is decision making theory by Richard Snyder about internal and external factors. This research shows that basically Thailand strongly support and encourage other countries to prepare to welcome the implementation of the policy. In addition, Thailand contributed to cooperate and assist countries in order to accelerate the implementation of the single visa scheme throughout Southeast Asia. Thailand started to implement single visa policy with Cambodia. Key words : Policy, ASEAN Tourism Forum, Participate, Thailand.